Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Kulit Telur Ayam Ras Melalui Metode Hidrotermal - Fadly Sitohang; Yelmida Azis; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite Ca10(PO4)6(OH)2 is a calcium phosphate compound which is bioactive ceramic material with high bioafinitas and the principal inorganic constituent of bones and teeth. Hydroxyapatite (HAp) materials use as bone implants, adsorbents and catalysts. In this research synthesis of hydroxyapatite can be made by using material which is rich of CaCO3 like PCC chicken’s egg shell with a composition of 99,45% CaCO3. PCC chicken’s egg shell which has calcium source synthesized to HAp by hydrothermal process with variated times of reaction (14 hours; 16 hours; 18 hours) and reaction temperature (130oC, 150oC, 170oC). HAp synthesized results have been analyzed by using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The results of FTIR analysis showed the formation of hydroxyapatite in the presence of peaks PO43- dan OH-. The highest peak obtained at reaction temperature 130oC with reaction time 14 hours and 16 hours. XRD diffraction results in hydroxyapatite got the highest purity obtained at temperature of 130oC at reaction time 14 hours with a hexagonal crystal structures. The results of SEM-EDX analysis showed that the morphology form of HAp was agglomerates or clumping . The molar ratio of Ca / P of hydroxyapatite which is made from chicken’s egg shell through the PCC was 1,69..Keywords : PCC Chicken’s Eggs Shell, pH, Temperature, Hydroxyapatite, Hydrothermal Method.